Gesture Controlled Chair - S. N. Musale; Arti R. Kondhalkar; Gaurav D. Kopnar (International Journal of Electronics Automation, 2026)
The Gesture Controlled Chair is a state-of-the-art assistive device that allows users to control the movements of their wheelchair with ease and efficiency using hand gestures. The existing technologies for controlling wheelchairs have been manual controls that require a certain level of physical strength, making them less suitable for elderly patients or those with physical disabilities. In this regard, a gesture-controlled interface was introduced as an alternative to the existing technologies to enhance the convenience and usability of such devices. The system consists of an MPU6050 sensor placed on the user’s hand that captures the movement and direction of the hand in real-time. The sensor is used to detect the tilt and motion along the different planes, which are then processed by an Arduino Uno controller to generate particular actions based on threshold values. The processed commands are sent through a wireless connection to a receiver that utilizes an HC- 05 Bluetooth module attached to the wheelchair. On the receiver’s side, another Arduino Uno microcontroller decodes the signal into control commands which are fed to the driver circuit. The L293D motor driver chip serves as a means to communicate the commands from the microcontroller to the DC motors for controlling the direction and speed of motors. Accordingly, depending on the command sent by the system, the motors control the movement of the wheelchair in the specified direction. Experimental results indicate that the proposed system provides gesture recognition with high accuracy around 85–95%.
Keywords: Arduino uno; Bluetooth commu- nication; Embedded system; Intelligent Wheelchair; MPU6050 sensor; Mobility Aid; gesture control